2014
DOI: 10.1123/jsm.2013-0046
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Influence of Proximal Networks on High School Athletes’ Intentions to Use Androgenic Anabolic Steroids

Abstract: Understanding what influences adolescent athletes is important for managers designing anti-doping initiatives. It is commonly assumed that elite athletes who dope influence adolescent athletes to similarly dope. Using the theory of normative social behavior, the effect of norms on adolescent athletes' intentions to use steroids was examined. The social distance between respondents and the source of normative information was systematically varied to include four separate levels (friends, teammates, college athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Neighbors et al () varied the social distance of reference groups and found that when participants' reference groups were proximal, normative influence on drinking behaviors was stronger. Woolf et al (), who investigated high school athletes' use of steroids as a function of their perceptions about use of steroids by others who varied on social proximity (friends, teammates, college athletes, and professional athletes), reported similar findings: Norms emanating from those perceived to be most proximal were strongest in influencing intention to use steroids.…”
Section: Interpersonal‐ and Societal‐level Moderatorsmentioning
confidence: 87%
See 1 more Smart Citation
“…Neighbors et al () varied the social distance of reference groups and found that when participants' reference groups were proximal, normative influence on drinking behaviors was stronger. Woolf et al (), who investigated high school athletes' use of steroids as a function of their perceptions about use of steroids by others who varied on social proximity (friends, teammates, college athletes, and professional athletes), reported similar findings: Norms emanating from those perceived to be most proximal were strongest in influencing intention to use steroids.…”
Section: Interpersonal‐ and Societal‐level Moderatorsmentioning
confidence: 87%
“…Although empirical evidence supports this prediction (Rimal, ; Smith & Louis, ), findings do not always conform to this pattern. Studies of alcohol consumption have shown a direct effect of injunctive norms on behavioral intent and no significant moderating effect of injunctive norms on the descriptive norm‐behavior relationship (Rimal & Real, ; Woolf, Rimal, & Sripad, ). For handwashing, descriptive norms were found to be positively associated with the behavior when strong injunctive norms were present, but descriptive norms were negatively associated with the behavior in the presence of weak injunctive norms (Lapinski, Anderson, Shugart, & Todd, ).…”
Section: The Tnsbmentioning
confidence: 99%
“…These results match those of similar studies performed previously (Engelberg & Skinner, 2016;Copeland & Potwarka, 2016;Barkoukis, Tsorbarzoudis & Rodafinos, 2013), which revealed the importance of individuals' milieu or social relations and their attitudes towards doping. A study with similar features performed by Woolf, Rimal and Sripad (2013) inquired into the possible causes of the use of anabolic steroids or other steroids in young people; 404 adolescent athletes participated in this study, which found that the norms and judgements of their friends or teammates are one of the factors that has most influence on the decision to use performance-enhancing drugs. However, there are also studies like the one by Pardo (2015) in which the majority of the athletes interviewed claimed that their teammates or peers did not influence them in this decision.…”
Section: Discussionmentioning
confidence: 99%
“…The typology includes four ideal types, but recognizes that there is much further variation in characteristics and approaches to AAS use. Beliefs about appearance and AAS (Bloodworth, Petroczi, Bailey, Pearce, & McNamee, 2012;Judge et al, 2012;Lucidi et al, 2008) and their use by others (Woolf, Rimal, & Sripad, 2014) have been identified as important and attitudes are likely to be reinforced or changed through personal experience over time. It is commonly identified that individuals may initiate use of AAS to overcome perceived genetic physical limitations (Grogan, Shepherd, Evans, Wright, & Hunter, 2006;Hanley Santos & Coomber, 2017;Kimergård, 2014;Van Hout & Kean, 2015).…”
Section: Individual Levelmentioning
confidence: 99%